Attenuation Of The Hemodynamic Response To Tracheal Intubation A Comparative Study Between Intra Venous Lignocaine Hydrochloride And Intravenous Magnesium Sulphate - Mohammad, Nik Marzuki (2001)
A standardized anesthetic technique was used for both groups of patients. An indwelling venous cannula was inserted under local anesthesia and a running intravenous drip was set. Vital signs monitoring were monitored and chartered before induction which served as a baseline to the hemodynamic changes expected to be seen at different stages of the induction period. Induction of anesthesia was perfonned by uSing sodium thipentone 2.5% solution titrated to the loss of the eye lash reflex, the study drugs of each allocated popUlation sample was administered accordingly and a single attempt at cannulation of the endotracheal tube by a single operator through out the study was performed 3 minutes after the neuromuscular blocking agent was given. Anesthesia